Arbitration law and practice in Albania: Features, challenges and perspectives - Gjuzi Jola (Strani pravni život)
Arbitration, as an alternative dispute resolution mechanism, has gained significant traction worldwide. This is primarily due to its consensual nature, the involvement of non-governmental adjudicators, as well as its efficiency, flexibility and confidentiality. In Albania, international arbitration remains a promising avenue for resolving commercial and investor-state disputes, especially considering the country's efforts towards a consolidated market and deeper integration into the regional and global economy. However, the arbitration landscape, particularly the domestic one, is not without challenges as Albania pursues to attain an effective rule of law. This paper provides an overview of the rules of arbitration under the Albanian domestic law, as well as the applicable international law. It then explores the current state of arbitration practice in Albania, the various perceptions among the pertinent political, business and legal communities, the challenges this practice encounters, and perspectives for its progress.